Local Community Participation In The Development Of The Mawun Beach Area, Central Lombok - Hafizi, Hafit; I Ketut Antara; Gde Indra Bhaskara (International Journal of Education, Vocational and Social Science, 2025)
This study aims to examine the forms of community participation and local empowerment in the development of the Mawun Beach tourism area, Central Lombok Regency. The research focuses on three key aspects: tourism development, community participation, and local empowerment in creating inclusive and sustainable tourism. A descriptive qualitative approach was employed, utilizing primary and secondary data collected through direct observation, in-depth interviews, and documentation. Data were analyzed using tourism development theory based on five indicators: attractions, transportation, accommodation, service facilities, and infrastructure. Additionally, the study applied community participation theory comprising seven typologies (manipulative, passive, consultation, material incentive, functional, interactive, and self-mobilization) and community empowerment theory with six dimensions (authority, competence, trust, opportunity, responsibility, and support). Findings indicate significant progress in attractions and local culture, while transportation and infrastructure remain limited. Community involvement reflects five participation forms, dominated by a top-down approach. Empowerment efforts have emerged through Pokdarwis and local groups, enhancing capacity and collective responsibility toward sustainable community-based tourism development. This study aims to examine the forms of community participation and local empowerment in the development of the Mawun Beach tourism area, Central Lombok Regency. The research focuses on three key aspects: tourism development, community participation, and local empowerment in creating inclusive and sustainable tourism. A descriptive qualitative approach was employed, utilizing primary and secondary data collected through direct observation, in-depth interviews, and documentation. Data were analyzed using tourism development theory based on five indicators: attractions, transportation, accommodation, service facilities, and infrastructure. Additionally, the study applied community participation theory comprising seven typologies (manipulative, passive, consultation, material incentive, functional, interactive, and self-mobilization) and community empowerment theory with six dimensions (authority, competence, trust, opportunity, responsibility, and support). Findings indicate significant progress in attractions and local culture, while transportation and infrastructure remain limited. Community involvement reflects five participation forms, dominated by a top-down approach. Empowerment efforts have emerged through Pokdarwis and local groups, enhancing capacity and collective responsibility toward sustainable community-based tourism development.